Promoting emotional skills in early adolescents with mental health conditions in music therapy - a content analysis of focus group interviews - Salokivi Maija; Salanterä Sanna; Saarikallio Suvi; Ala-Ruona Esa (GRIEG ACADEMY, 2025)
Introduction
Music therapy is actively used with early adolescents in relation to their emotional skill development. Yet, the conceptualization of emotional skills is typically not systematically addressed in therapeutic practice. This study examined music therapists' views on the progress of emotional skills when working with early adolescents with mental health conditions. The study also explored what kind of methods the therapists use with the target group, and the applicability of a previously published conceptual model.
Method
We conducted a deductive-inductive content analysis of transcripts from four focus group interviews among 13 professional music therapists.
Results
The therapists concluded that the progress of the emotional skills of their clients can be seen both in daily functioning as well as the client's functioning in therapy. The selection of therapy methods was broad and included both music-based and non-music-based methods. Therapists considered the presented conceptualization of emotional skills to be valid, but had difficulty examining their practices using all levels of the model. Several practical features were identified that were considered beneficial for the therapists in clinical practice.
Discussion
This study adds to knowledge about the progress of emotional skill development, working methods, and useful perspectives for working on emotional skills in early adolescents with mental health conditions. The conceptual model of emotional skills can offer a tool for helping music therapists define, observe and analyse emotional skills in the therapy context.